Clinical and paraclinical features, outcome, and prognosis of ovarian granulosa cell tumor: A retrospective study of 28 Vietnamese women - Duc Thanh Le; Tu Anh Do; Linh Ly Thi Nguyen; Kien Hung Do; Chu Van Nguyen (Rare Tumors, 2022)
Background: Granulosa cell tumor of the ovary is a rare disease and presents with two clinically and molecularly distinct subtypes: the juvenile and the adult type. GCT is considered as a malignant tumor with an indolent course and a tendency toward late recurrence. Purpose : To assess the clinical and paraclinical features, treatment findings, survival outcomes, and explored the prognostic factors in the granulosa cell tumor. Methods : The current study was conducted on 28 GCT patients who had surgical operations and adjuvant chemotherapy (stage IC-IV) by applying a retrospective cohort analysis. The clinical and paraclinical characteristics were recorded. Recurrent status was evaluated for analysis with clinical and paraclinical features and survival. All GCT patients’ survival were analyzed by using Kaplan-Meier and Log-Rank models. Results : 17.9% of patients experienced a relapse and two patients died due to disease. The mean time from initial diagnose to recurrence was 40.21 months. The 5-year OS and DFS of stage I-II were 100% and 80.8%, and of stage III were 50% and 25%, respectively. In survival analyses, using the log-rank test, age ≥50 years, irregular menstruation, stage I-II, and absence of residual lesion were all significant predictors for the improved DFS. Stage I-II and absence of residual lesion were associated significantly with better OS. Mean of age, FIGO stage, and residual lesion during surgery had significant differences to recurrent rate (p < <0.05). The multivariate model revealed that these factors didn’t remain as an independent prognostic variable. Conclusion : FIGO stage and residual lesion during surgery had significant differences in survival and recurrent rate.